2020
DOI: 10.1038/s41598-020-74361-w
|View full text |Cite
|
Sign up to set email alerts
|

Dyke apertures record stress accumulation during sustained volcanism

Abstract: The feedback between dyke and sill intrusions and the evolution of stresses within volcanic systems is poorly understood, despite its importance for magma transport and volcano instability. Long-lived ocean island volcanoes are crosscut by thousands of dykes, which must be accommodated through a combination of flank slip and visco-elastic deformation. Flank slip is dominant in some volcanoes (e.g., Kilauea), but how intrusions are accommodated in other volcanic systems remains unknown. Here we apply digital ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Dike intrusions are widespread on the Canary Islands, an archipelago with seven main islands located in the Atlantic Ocean. Dikes in the Canaries have mainly been studied in deeply eroded valleys and excavated road cuts and tunnels, indicative of ancient principal stress fields, rift zones and flank movements [Carracedo 1994;Day et al 1999;Gudmundsson et al 1999;Ablay and Martı 2000;Walter and Schmincke 2002;Ancochea et al 2003;Fernández et al 2006;Ancochea et al 2008;Galindo and Gudmundsson 2012;Thiele et al 2020]. Mapping of hundreds to thousands of dikes on La Palma showed that they have a median thickness of ∼1 m at depth [Thiele et al 2020], which is in agreement with measurements done at other Canary Islands [Marinoni and Gudmundsson 2000].…”
Section: Introductionsupporting
confidence: 67%
“…Dike intrusions are widespread on the Canary Islands, an archipelago with seven main islands located in the Atlantic Ocean. Dikes in the Canaries have mainly been studied in deeply eroded valleys and excavated road cuts and tunnels, indicative of ancient principal stress fields, rift zones and flank movements [Carracedo 1994;Day et al 1999;Gudmundsson et al 1999;Ablay and Martı 2000;Walter and Schmincke 2002;Ancochea et al 2003;Fernández et al 2006;Ancochea et al 2008;Galindo and Gudmundsson 2012;Thiele et al 2020]. Mapping of hundreds to thousands of dikes on La Palma showed that they have a median thickness of ∼1 m at depth [Thiele et al 2020], which is in agreement with measurements done at other Canary Islands [Marinoni and Gudmundsson 2000].…”
Section: Introductionsupporting
confidence: 67%
“…Previous studies indicate that short-term storage reservoirs formed at shallow depths (2–5 km) weeks-to-days before the eruptions 36 , 37 . Our results show that the shallow accumulation of magma below Jedey (at ~ 1–5 km) started ~ 3.5 months before the eruption, which can be related with the earliest eruption products 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The Taburiente dykes radiate from a focal point in the southern part of the caldera, as described in detail in Thiele et al. (2020). Along the northern side of the caldera these dykes crosscut an earlier NE striking and shallower‐dipping (∼45–60°) dyke set interpreted to have formed relatively early in the growth of Volcán Taburiente (Thiele et al., 2020).…”
Section: The Taburiente Dyke Swarmmentioning
confidence: 99%
“…Bemis et al., 2014; Dering et al., 2019). These digital outcrop models and details of the methods used to construct them are described in (Thiele​ et al., 2019, 2020). For this study, we focus on three surveys from a site known locally as Hoyo Verde (Figure 1a), where dykes of different orientations intersect to form multi‐dykes (Figure 1b).…”
Section: Field Observations and Mappingmentioning
confidence: 99%